Economic Benefit Evaluation and Analysis Based on Intelligent Agriculture Internet of Things - Shu Liu; Yuting Wu (Journal of Mathematics)
There has been a consensus on the development of ecological agriculture to promote the leap from traditional agriculture to ecological agriculture, but the unavoidable fact is that the development of ecological agriculture is still relatively slow at the present stage and has not formed a major climate and great influence. The rise of the Internet is a technology that has promoted the transformation and upgrading of modern agriculture, changed the traditional agricultural production mode, and accelerated the scientific and technological integration of information. In view of the characteristics and difficulties of agriculture, this paper builds an Agricultural Internet of Things (IoT) management system to realize the integrated management of Internet equipment and realize the management of environmental data, video data, and agricultural expert knowledge. Then from perception technology, transmission technology, and the perspective of three intelligent information processing technologies, this paper introduces the present state of agricultural IoT, analyzes the Internet of Things to the economic benefits of agricultural production, to research the problems of China’s agricultural development of the Internet of Things, and puts forward China’s agricultural Internet of the future research emphasis and direction of development.